Effect of some myostatin (MSTN) variants on live weight and beef traits measured by ultrasound in Charolais candidate breeding bulls - Ferenc Szabó; Gabriella Holló; Tamás Csürhés; Márton Török; Károly Tempfli; Edit Mikó; Szabolcs Bene (Journal of Applied Animal Research)
This study investigated the relationship between some ultrasound measurements, live weight data, and five (F94L, nt267, nt324, nt414 and Q204X) myostatin (MSTN) variants associated with beef production in Charolais cattle. A total of 390 Charolais candidate breeding bulls were weighed at birth (BIW) as well as 205 (CWW) and 400 days (FDW) of age, and ultrasonically measured for ribeye area (REA), fat thickness at rump (FRU), fat thickness at ribeye (FRI) and marbling of the ribeye (MAR) at 400 days of age. The frequency of allele C and A were high in the studied population. The F94L had a significant effect on the FRU and FRI, whereas REA significant differed between homozygous and heterozygous animals on SNP at nt267. MAR of non-mutant animals were significantly (by 04.−05 points) lower than those heterozygous for the F94L. FRI tended to be higher (0.51–0.57 cm) for mutations together nt267 and nt414, or for F94L, nt414 and nt324, but lower (0.47–0.49 cm) for nt267 and nt414 mutations. The results indicating F94L could be use in QTL selection for improving beef quality. The polygenetic effect of different MSTN mutations, as well as the effect of MSTN deficiency, would be worth investigating in the future.